SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-4033
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Preparation and Combustion Variability in a Spray-Guided DISI Engine

Abstract: In an attempt to study the numerous contributors towards cyclic variations in combustion in a direct injection spark ignition engine, simultaneous high-speed imaging of fuel injection and flame growth are undertaken on a crankangle resolved basis in a single-cylinder optical research engine. Batches of images from 100 consecutive cycles are acquired for all conditions with synchronised incylinder pressure logging. The engine is motored and fired at stoichiometric conditions at 1500 RPM under part-load and wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 27 publications
3
61
0
Order By: Relevance
“…more liquid in the footprint) when viewed from the chamber base (equivalent to the piston crown in an engine). It should be borne in mind that the injector is mounted at an angle of 19° in the chamber and hence the view shown in the images is angled to that which would be seen from the piston crown in an engine, as presented in [12]. Figure 23 shows the total spray area as seen from the base view during spray development from 'first fuel' seen (333 μs ASOI) to a fully-developed spray form (1110 μs ASOI).…”
Section: Resultsmentioning
confidence: 99%
“…more liquid in the footprint) when viewed from the chamber base (equivalent to the piston crown in an engine). It should be borne in mind that the injector is mounted at an angle of 19° in the chamber and hence the view shown in the images is angled to that which would be seen from the piston crown in an engine, as presented in [12]. Figure 23 shows the total spray area as seen from the base view during spray development from 'first fuel' seen (333 μs ASOI) to a fully-developed spray form (1110 μs ASOI).…”
Section: Resultsmentioning
confidence: 99%
“…one at the intake side and the other at the exhaust side of the engine. More details about the injector geometry, nozzle-hole angles and spray formation in a quiescent environment and in a running DISI engine can be found in previous studies by the current authors [3,4,[8][9][10].…”
Section: Injectormentioning
confidence: 99%
“…towards the spark plug or any other in-cylinder area of interest, and by flexibility of when and how fuel is injected into the cylinder i.e. independence over piston position [2][3][4].…”
Section: Injection Systems For Direct-injection Spark-ignition Enginesmentioning
confidence: 99%
“…This was achieved using a real-size optical nozzle to simulate the flow in one of 8 the holes of a real multi-hole injector previously used by the authors for macroscopic spray imaging and related engine studies [22][23][24][25][26][27]. These studies showed that the geometry and break-up of sprays from such injectors is significantly affected by operating conditions, which result in a high degree of superheating of the fuel components, i.e.…”
Section: Present Contributionmentioning
confidence: 99%